Factor XII-dependent Contact Activation on Endothelial Cells and Binding Proteins gC1qR and Cytokeratin 1 - Joseph, Kusumam; Shibayama, Yoji; Ghebrehiwet, Berhane; Kaplan, Allen P. (Thrombosis and Haemostasis, 2001)
Although proteins of the kinin-forming pathway are bound along the surface of endothelial cells, the mechanism of activation of this proteolytic cascade is unclear. Endothelial cell surface proteins, gC1qR and cytokeratin 1, are capable of binding Factor XII and high molecular weight kininogen (HK) in a zinc-dependent reaction thus we considered the possibility that these proteins might catalyze initiation of the cascade. Incubation of Factor XII, prekallikrein, and HK with gC1qR or cytokeratin 1 leads to a zinc-dependent and Factor XII-dependent conversion of prekallikrein to kallikrein. We also demonstrate that normal plasma is capable of activating upon interaction with the cells whereas plasma deficient in Factor XII, prekallikrein and HK do not activate. Normal plasma activation was inhibitable by antibody to gC1qR and cytokeratin 1. Thus, gC1qR and cytokeratin 1, represent potential initiating surfaces for activation of the plasma kinin-forming cascade and may do so as a result of their expression along cell surfaces.
Keywords: Factor XII; HK; gC1qR; cytokeratin 1; endothelial cells